Heterojunctions and Nanostructures 2018
DOI: 10.5772/intechopen.75736
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization Cross Section in Low-Dimensional Systems

Abstract: A theoretical investigation of the effects of the parabolic, shifted parabolic, hill-like, and cup-like parabolic confining electric potentials on photoionization cross section (PCS) in a spherical quantum dot is presented. Each of the parabolic potentials is superimposed on an infinite spherical square quantum well (ISSQW) potential. The parabolic potential blueshifts the peaks of the PCS, while the shifted parabolic potential causes a redshift. As the so-called strength of cup-like parabolic potential is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…They observed that both the binding energy and the photoionization cross-section depended strongly on the layer thickness and photon energies. Based on the aforementioned observations that electronic and opto-electronic devices depend upon how electrons inside materials behave and how they are influenced by external perturbations which may be electrical [29][30][31], magneti c [32], electromagnetic, mechanical, hydrostatic pressure, this study has looked into the dynamic behavior of the photoionization cross-section. The variation of the photoionization cross-section with the incident photon frequency and with the position of the hydrogenic donor impurity in a square quantum well dot is determined using variational technique.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that both the binding energy and the photoionization cross-section depended strongly on the layer thickness and photon energies. Based on the aforementioned observations that electronic and opto-electronic devices depend upon how electrons inside materials behave and how they are influenced by external perturbations which may be electrical [29][30][31], magneti c [32], electromagnetic, mechanical, hydrostatic pressure, this study has looked into the dynamic behavior of the photoionization cross-section. The variation of the photoionization cross-section with the incident photon frequency and with the position of the hydrogenic donor impurity in a square quantum well dot is determined using variational technique.…”
Section: Introductionmentioning
confidence: 99%